Measurement of the polarisation of W bosons produced in top-quark decays using dilepton events at √s=13 TeV with the ATLAS experiment - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; et al. (Physics letters, 2023)
A measurement of the polarisation of W bosons produced in top-quark decays is presented, using proton-proton collision data at a centre-of-mass energy of √s=13 TeV. The data were collected by the ATLAS detector at the Large Hadron Collider and correspond to an integrated luminosity of 139 fb−1. The measurement is performed selecting tt¯ events decaying into final states with two charged leptons (electrons or muons) and at least two b-tagged jets. The polarisation is extracted from the differential cross-section distribution of the cos⁡θ⁎ variable, where θ⁎ is the angle between the momentum direction of the charged lepton from the W boson decay and the reversed momentum direction of the b-quark from the top-quark decay, both calculated in the W boson rest frame. Parton-level results, corrected for the detector acceptance and resolution, are presented for the cos⁡θ⁎ angle. The measured fractions of longitudinal, left- and right-handed polarisation states are found to be f0=0.684±0.005(stat.)±0.014(syst.), fL=0.318±0.003(stat.)±0.008(syst.) and fR=−0.002±0.002(stat.)±0.014(syst.), in agreement with the Standard Model prediction.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 03.06.2024